Dynamic control of urban sewer systems to reduce combined sewer overflows and their adverse impacts - Rathnayake, U.; Anwar, Faisal (ELSEVIER, 2019)
Sewer network planners use control algorithms, based on optimization techniques, to control urban wastewater systems. These control algorithms have been used to ease the stress on the sewer networks and then, to reduce or to minimize the combined sewer overflows (CSOs). CSOs are not only risking human health but also adversely affecting the aquatic lives. Therefore, many cities try to avoid CSOs. However, this cannot be done to the perfect level due to the capacity limitations of the existing combined sewer networks. In addition, climate variabilities have caused unpredictable precipitation increments and therefore, the control is extremely difficult. Therefore, considering the spatial and temporal variations of runoffs and qualities of stormwater generated from the precipitation, an enhanced optimal control algorithm is illustrated in this paper to control the existing combined sewer networks. Minimizing the pollution load to the receiving water and minimizing the cost of wastewater treatment and pump operation are the two objective functions in the developed optimization algorithm. The algorithm was then successfully applied to a real-world combined sewer network in Liverpool, United Kingdom. Results reveal that the developed optimal control model is capable of handling the dynamic control settings of combined sewer system to minimize the two objective functions simultaneously. With a little computational appreciation, the developed optimal control model can be well-used in the real-time control of combined sewer networks.